The Emerging Arctic Shipping Corridors. Issue 10 (17th May 2022) - Min, Chao; Yang, Qinghua; Chen, Dake; Yang, Yijun; Zhou, Xiangying; Shu, Qi; Liu, Jiping
Abstract: The dramatic sea ice loss makes trans‐Arctic navigation possible. However, navigability assessments at high temporal resolution are still very limited. To bridge this gap, daily sea ice concentration and thickness from CMIP6 projections are applied to evaluate the future potential of Arctic shipping under multiple climate scenarios. The September navigable area will continue to increase through the 2050s for open‐water (OW) ships and the 2040s for Polar Class 6 (PC6) vessels across all scenarios. Quasi‐equilibrium states will then ensue for both OW and PC6 ships under SSP245 and SSP585. The sailing time will be shortened, especially for OW ships, while the navigable days for both types of vessels will increase dramatically. PC6 ships will be able to sail the Arctic shipping routes year‐round starting in the 2070s when the decadal‐averaged global mean surface temperature anomaly hits approximately +3.6°C (under SSP585) compared to pre‐industrial times (1850–1900). Plain Language Summary: Trans‐Arctic shipping activities are increasing with the retreat of Arctic sea ice, thus, a systematic navigability assessment is urgently needed. We carried out this assessment at high temporal resolution. Shipping opportunities will increase substantially even under the sustainable green energy scenario (SSP126). Remarkably, Polar Class 6 ships are expected to sail the trans‐Arctic corridors year‐round starting in the 2070s under SSP585. For open‐water ships, the changes in September navigable area and in navigable days are not much different under SSP126 than under SSP245. The diversity of trends in the September navigable area under SSP126, SSP245, and SSP585 is markedly different from that of sea ice area/extent. The opening of shipping routes is strongly determined by the combined effects of sea ice thickness and concentration reductions. Key Points: The Arctic shipping opportunities for open‐water and Polar Class 6 (PC6) ships will increase substantially even under SSP126 The changes in September navigable area are markedly different from that of the sea ice area/extent derived from sea ice concentration only PC6 ships will sail trans‐Arctic shipping routes year‐round since the 2070s when the decadal‐averaged global mean surface temperature anomaly hits +3.6℃ under SSP585